Analysis of Risk Factors for Hypertension among the Productive Age Population - Husna Husna; Irfansyah Baharuddin Pakki; Ratih Wirapuspita (Indonesian Journal of Global Health Research, 2026)
Hypertension is a growing public health issue, particularly affecting individuals in productive age groups. The high incidence of hypertension in the North Sangatta Health Centre area highlights the need to identify contributing risk factors. This study aims to analyse determinants associated with hypertension among productive-age residents within the working area of the North Sangatta Health Centre. The method used in this study was an analytical observational approach with a case–control design. Data were collected using demographic questionnaires and blood pressure observation sheets. The research instruments were not subjected to validity and reliability testing because a digital sphygmomanometer that had been calibrated by the hospital and was used in accordance with standard operating procedures was utilized. The variables examined included demographic factors (age, sex, education, occupation), smoking habits, and medical history (familial hypertension and diabetes). The sampling technique used was non-random sampling, specifically purposive sampling, with a total of 136 respondents (68 cases and 68 controls). Data were analyzed using chi-square tests and logistic regression tests. Result: The findings indicated significant associations between hypertension and age (P < 0.000), diabetes (P < 0.001), and family history of hypertension (P = 0.009). No significant associations were found for gender (P = 0.859), occupation (P = 0.360), education (P = 0.069), or smoking habits (P = 0.170). Conclusion: It is concluded that age and specific medical and occupational factors play important roles in hypertension incidence in this population.